Adolescents: a paediatrician’s or an adult physician’s domain? clinical profile of Indian adolescents admitted in pediatric ward and those admitted in other than pediatric ward - Patel, Snehal V.; Vasavada, Halak J.; Patel, Purvi R.; Rathod, Nirav B. (International Journal of Contemporary Pediatrics, 2020)
Background: Study of the clinical profile and no. of admissions of adolescents admitted in pediatric ward and other than Pediatric ward. Methods: A Prospective Study, conducted during August 2018 to March 2019, at a tertiary care teaching hospital, including age group 10-19 years. Results: Out of 1645, highest adolescents’ admissions 749 (46.37%) were to medical ward, 2nd highest in the Pediatric ward which was 317 (19.6%), followed by general surgical ward which was 312(19.3%). Highest among late adolescents, infectious diseases were still the leading cause of hospitalization of adolescents as it constituted 68.4% (902) of admissions to other than pediatric ward followed by surgical cause[135(10.2%)] followed by accidents [5%(66)]. Conclusions: Infectious diseases are more common in adolescents compared to developed countries. The shift in hospitalisation of adolescents from pediatrics to general medicine at about 14 years is illustrated in present study and reflects the need of better implementation of clinical policy on the age divide.